Stool consistency is significantly associated with pain perception. - Yukiko Shiro; Young-Chang Arai; Tatsunori Ikemoto; Kazuhiro Hayashi (PLoS ONE)
Background Commensal as well as pathogenic bacteria can influence a variety of gut functions, thereby leading to constipation and diarrhea in severe cases. In fact, several researchers have reported evidence supporting the association between stool consistency or constipation and the Gut microbiome (GM) composition and dysbiosis. GM influences the human health and disease via the gut-brain axis. We thus hypothesized that the pathogenic bacteria increases pain perception to some extent, which means that there could be an association between stool consistency or constipation and pain perception of healthy subjects. Design Observational study. Objectives The aim of the present study was to investigate the association between stool consistency or constipation and pain perception of healthy subjects. Methods Thirty-eight healthy subjects participated in this study. The participants were assessed on their usual stool form (the Bristol Stool Form Scale: BSFS), constipation (the Cleveland Clinic Constipation score: CCS), degree of obesity, pain perception by mechanical stimulus, cold pain threshold, and a questionnaire on psychological state. Results The BSFS was significantly and positively associated with pain perception, and showed a significant association with anxiety states. Furthermore, pain perception was significantly associated with anxiety states. However, there were no significant associations between the CCS and any independent variables. In addition, we found that a significant predictor to the pain perception was BSFS. Moreover, there were significant relationships among the psychological states, BSFS and obesity. Conclusion These results suggest that the stool form is associated with pain perception and anxiety status.